A test for the redshift dependence of $$σ _8$$ σ 8 using $$fσ _8$$ f σ 8 measurements - Siddhant Manna; Shantanu Desai (European Physical Journal C: Particles and Fields, 2024)
Abstract We search for a redshift dependence of $$σ _8^0$$ σ 8 0 using 23 growth rate measurements from redshift space distortions and peculiar velocity measurements as a consistency check of $$Λ $$ Λ CDM. For this purpose we use the dataset from Sagredo et al. (Phys Rev D 98:083543, 2018) consisting of 22 measurements, which has been vetted for internal consistencies. Eighteen of these measurements have been obtained from the Gold-2017 sample, collated from multiple redshift space distortion surveys between 2009 and 2016, whereas the remaining four have been obtained from the eBOSS DR14 quasar survey. We also added one additional data point from the BOSS DR12 CMASS galaxy sample. We find that for this dataset the $$σ _8^0$$ σ 8 0 values are consistent between the low redshift and high redshift samples using three different redshift cuts. This implies that the growth rate measurements are consistent with a constant $$σ _8^0$$ σ 8 0 in accord with $$Λ $$ Λ CDM, assuming there are no uncontrolled systematics in this dataset.